Relationship between tau-PET and quantitative susceptibility mapping in atypical Alzheimer’s disease - Neha Singh-Reilly; Ryota Satoh; Jonathan Graff-Radford; Mary M. Machulda; Val J. Lowe; Keith A. Josephs; Jennifer L. Whitwell (Frontiers in Aging Neuroscience)
BackgroundIron is an important component in neurofibrillary tangles, is known to co-localize with tangles in Alzheimer’s disease (AD) and can be measured using quantitative susceptibility mapping (QSM). However, it is unclear if iron measured using QSM is regionally related to tau in atypical presentations of AD.MethodsForty patients with atypical AD underwent a 3 T magnetic resonance imaging (MRI) scan with a five-echo gradient echo sequence to calculate QSM, Aβ, and [18F] AV-1451 positron emission tomography (PET). The relationship between QSM and tau-PET was assessed using voxel-based regression analysis using whole brain VoxelStats and region-of-interest (ROI)-based Spearman’s correlation analyses using cortical and subcortical ROIs.ResultsAt the voxel-level, positive correlations between tau-PET and QSM were only observed in the left caudate. At the ROI-level, a positive association was observed between tau-PET and susceptibility in the occipital lobe and a negative association was observed between substantia nigra susceptibility and occipital tau-PET uptake, although these findings did not survive correction for multiple comparisons.DiscussionOur data provides little evidence that regional tau-PET uptake is related to susceptibility changes, suggesting that iron deposition may not be directly associated with tau accumulation in atypical AD.